A five‐year retrospective analysis of adherence in cystic fibrosis. Issue 12 (7th September 2015) - Shakkottai, Aarti; Kidwell, Kelley M.; Townsend, Monica; Nasr, Samya Z.
Summary: Objective: We conducted a retrospective analysis of medication adherence and health outcomes over a 5‐year period in children with cystic fibrosis (CF). Methods: Adherence was calculated for several commonly prescribed CF medications by comparing the actual number of times a prescription was filled in a 12‐month period to the number of times it should have been filled based on the prescribed supply. We used prescription refill histories as documented by three major specialty pharmacies used by our patients. A binomial mixed effects model was used to investigate the longitudinal association between adherence and age group (0–5, 6–12, and 13–21 years) with gender, year in the study, lung function, body mass index (BMI), and annual hospitalization rate included as potential confounders. Results: The 0–5 years group had the highest overall adherence ( P  = 0.009). The 6–12 years group had significantly better adherence to inhaled medications as compared to oral medications ( P  = 0.020). Within each group, for any given year in the study, having a higher BMI was associated with greater odds of adherence ( P  < 0.0001). There were no associations between adherence and gender, lung function or hospitalization rate ( P  > 0.05). Conclusions: There are significant age differences in adherence. Younger patients have better overall adherence likely secondary to increased parental supervision. Having better nutritional status is associated with improved adherence.Pediatr Pulmonol. 2015; 50:1224–1229. © 2015 Wiley Periodicals, Inc.